2001
DOI: 10.1007/bf02982064
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic Study of Idarubicin in Japanese Patients With Malignant Lymphoma: Relationship With Leukocytopenia and Neutropenia

Abstract: To clarify the pharmacokinetic properties of idarubicin (IDA) in Japanese patients and to clarify the relationship between the pharmacokinetic parameters of IDA or idarubicinol (IDAol), an active metabolite of IDA, and leukocytopenia or neutropenia, we examined the pharmacokinetics of IDA in patients with malignant lymphoma. Nine of 21 patients registered in an early phase II study of IDA were enrolled in the pharmacokinetic study. IDA (12 or 15 mg/m2) was administered by intravenous infusion for 5 minutes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Immediately after injection of the emulsion, we did not detect any idarubicin in the plasma; it took at least a few minutes for the drug to appear. When compared with data in the literature, our findings highlighted the improved PK profile of idarubicin c-TACE compared with both doxorubicin c-TACE (mean C max 10 times lower [7]) and idarubicin IV injection (mean AUC 0-24h three times lower [33]), and also showed that the in vivo release of idarubicin from a lipiodol-based emulsion was very close to that observed from DEEs [23,34] (Table 4). The first peak of idarubicinol concentration between 5 and 10 min after injection of the emulsion can be explained by the very quick extraction of part of the idarubicin by hepatocytes followed by its immediate metabolisation.…”
Section: Discussionsupporting
confidence: 83%
“…Immediately after injection of the emulsion, we did not detect any idarubicin in the plasma; it took at least a few minutes for the drug to appear. When compared with data in the literature, our findings highlighted the improved PK profile of idarubicin c-TACE compared with both doxorubicin c-TACE (mean C max 10 times lower [7]) and idarubicin IV injection (mean AUC 0-24h three times lower [33]), and also showed that the in vivo release of idarubicin from a lipiodol-based emulsion was very close to that observed from DEEs [23,34] (Table 4). The first peak of idarubicinol concentration between 5 and 10 min after injection of the emulsion can be explained by the very quick extraction of part of the idarubicin by hepatocytes followed by its immediate metabolisation.…”
Section: Discussionsupporting
confidence: 83%